Observation of Resistive Switching Memory by Reducing Device Size in a New Cr/CrO x /TiO x /TiN Structure - Jana, Debanjan; Samanta, Subhranu; Roy, Sourav; Lin, Yu Feng; Maikap, Siddheswar (Nano-Micro Letters, 2015)
The resistive switching memory characteristics of 100 randomly measured devices were observed by reducing device size in a Cr/CrO x /TiO x /TiN structure for the first time. Transmission electron microscope image confirmed a via-hole size of 0.4 µm. A 3-nm-thick amorphous TiO x with 4-nm-thick polycrystalline CrO x layer was observed. A small 0.4-µm device shows reversible resistive switching at a current compliance of 300 µA as compared to other larger size devices (1–8 µm) owing to reduction of leakage current through the TiO x layer. Good device-to-device uniformity with a yield of >85 % has been clarified by weibull distribution owing to higher slope/shape factor. The switching mechanism is based on oxygen vacancy migration from the CrO x layer and filament formation/rupture in the TiO x layer. Long read pulse endurance of >105 cycles, good data retention of 6 h, and a program/erase speed of 1 µs pulse width have been obtained.